Risk management technologies in the development of social activity of the youth - Irina V. Arendachuk; Milena A. Klenova (Saratov State University, 2022)
The article presents the results of the study aimed at justifying the possibility to use risk management technologies in working with young people in order to support their social activity. The study hypothesis is based on the assumption that modern risk management technologies, which are interdisciplinary in nature, can be used when working with young people, contributing to the formation and development of constructive forms of their social activity. Research methods: subject-categorical analysis; analysis of theoretical and empirical research on the problems of young people's social activity and risk management in various spheres of social life. The study proposes an interdisciplinary approach in order to determine the main vectors of the risk management directions in the development of social activity of an individual. The research indicates the main zones and sources of young people's risks that are associated with manifestation of various forms of social activity in modern conditions of Russian society. Technologies of risk analysis, assessment and management are analyzed in relation to the problem of social activity of young people. The authors consider the applied aspects of implementing these technologies when working with young people using the example of civic, and educational and developmental activity. The study shows that methods, forms and the structure of risk management are universal and can be used in risk management in the social activity development.